Effect of protein supplementation on some rumen parameters in cattle (Semiárida, 2020)
The objective of this study was to measure the effect of soya bean supplementation on some ruminal parameters. A diet composed of rye grass hay was given to Holstein-Freisian dry cows fitted with permanent rumen fistulae, with (CS) or without (SS) supplementation of 1 Kg soya bean meal per cow day. Samples of rumen content were withdrawn at 0, 2,4, 6,8; and 10 hours after supplementation, simultaneously for both treatments. The samples were processed for: ammonia, ATP and volatile fatty acids (AGV) concentration, AGV composition and rumen bacterial counts. Significant differences between treatments were found for ammonia concentration (CS: 86.4 mg/l; ss. 53.7 mg/I; P
Keywords: protein supplementation; soya bean meal; ruminal parameters